Slime as Playing Therapy on Response of Biological, Psycological and Eating Behaviour of Preschool in Hospital - Maria Yashinta Seran; Ilya Krisnana; Praba Diyan Racmawati (Pediomaternal Nursing Journal, 2019)
Introduction: Slime is one of the toys that many kids like because it was adorable with a variety of bright and colorful color variations. The purpose of this study was to determine the effect of slime play therapy on biological, psychological, and eating behavior in preschool children who undergo hospitalization in the Dahlia Room of RSUD Mgr. Gabriel Manek, SVD Atambua.Methods: This research used quasi experiment with post-test only non-equivalent control group design. The total population was 90 patients with a sample size of 60 respondents, divided into 30 treatment groups and 30 control groups. The sample was determined by consecutive sampling technique. The independent variable was slime play therapy. The dependent variable was biological, psychological, and eating behavior. Data were obtained by observation sheet and Child Eating Behavior Questionnaire (CEBQ) instrument and data were analyzed by the Mann-Whitney U Test.Results: There were differences between the treatment group and the control group on respiratory frequency (p=0.021), pulse frequency (p=0.002), stress (p=0.035), and eating behavior (p=0.041).Conclusion: Slime play therapy was an atraumatic care approach that can be used to reduce stress level hospitalization, biological responses to normal, and eating behavior to be good for children who were hospitalized.